Endocannabinoid signaling regulates post-operative delirium through glutamatergic mediodorsal thalamus-prelimbic prefrontal cortical projection - Liu, Yang; Jia, Sansan; Wang, Jiajia; Wang, Dan; Zhang, Xinxin; Liu, Huiqing; Zhou, Fang; Zhang, Zhihao; Li, Qi; Dong, Hailong; Zhong, Haixing (Frontiers in Aging Neuroscience, 2022)
Background Postoperative delirium (POD), a common postoperative complication that affects up to 73.5% of surgical patients, could prolong hospital stays, triple mortality rates and cause long-term cognitive decline. However, the underlying mechanisms remain largely unclear. Previous studies demonstrated that cannabis use might cause delirium-like behavior through the endocannabinoid system (eCBs). We also found that prefrontal cortex (PFC) was involved in the eCBs associated general anesthesia recovery. Objectives The present study was aimed to investigate the role of eCBs in POD development, and further clarify its neuronal specificity and circuit specificity attributed to POD. Methods 2 hours of 1.4% isoflurane anesthesia and simple laparotomy were conducted to establish the POD model in 4-month-old C57/BL6 mice. A battery of behavioral tests, including the buried food, open field, and Y maze tests, were performed 24 hours before and 6, 9 hours after anesthesia and surgery (AS). The behavioral results were calculated as composite Z score for POD assessment. To explore the dynamics of eCBs and its effect on POD regulation, endocannabinoid (eCB) sensor was microinjected into the PFC, and the antagonists of type 1 cannabinoid receptor (CB1R), were administered. Chemogenetics were employed in mutant mice for neuronal and circuit specificity observation. Results After AS, the composite Z score significantly increased at 6 and 9 hours but not 24h, whereas blockade of CB1R systemically and intra PFC could specifically decrease the composite Z score at 6 and 9 hours after AS. Fiber photometry confirmed that the activity of eCB in PFC was enhanced by AS. Moreover, activation of glutamatergic neurons in PFC could reduce the composite Z score, which could be significantly reversed by exogenous cannabinoid (nabilone). Further study revealed the glutamatergic projection from mediodorsal thalamus (MD) to PFC glutamatergic neurons was in charge of the effect of eCBs on POD. Conclusion Our study firstly demonstrated the involvement of eCBs in the POD pathogenesis, and further revealed that the eCBs may regulate POD through the specific MDglu-PFCglu circuit. These findings not only partly revealed the molecular and circuit mechanisms of POD, but also provide an applicable candidate for clinical prevention and treatment of POD.